Nigeria Economic Report, No. 1, May 2013 - World Bank (Washington, DC, 2014)
The Nigeria economic report represents a new World Bank product intended to be produced on a biannual basis. Each report will provide an assessment of the current economic situation in the country and give special attention to selected topics of high policy relevance for Nigeria. This first Nigeria economic report will give some attention to longer term trends in the country, including the puzzle of why a decade of rapid Gross Domestic Product (GDP) growth by official statistics, concentrated in the pro-poor areas of agriculture and trade, did not bring stronger welfare and employment benefits to the population. The second chapter of this Report turns to the question of Government oil revenues and related future budgetary challenges to the country. Due to relatively slow expected growth in oil production and the real appreciation of the naira, the share of Government oil revenues in GDP fell significantly in 2012, and will likely continue to fall in the medium term. The third chapter addresses a question that has been at the center of many recent controversies and initiatives in Nigeria: fiscal federalist relations. The chapter argues that the current basic model of fiscal federalism may actually suit Nigeria very well, and could be consistent with the rapid successful development of the country. But the success of this model will depend on developing mechanisms for better cooperation between the federal and state governments in three key areas: (a) effective macroeconomic management of the country's oil wealth, (b) the coordination of fiscal policies, particularly for the connectivity of markets and improvement of public services, and (c) the realization of national standards for accounting and disclosure of information.